CORPORATE GOVERNANCE DAN PENGARUHNYA TERHADAP KINERJA KEUANGAN PERUSAHAAN - Gie, Emilia (IAIN Langsa, 2019)
Application of corporate governance in the company is a way to handle the agency con?ict that impact to company?s ?nancial performance The objective of this research is to analyses the impact of managerial ownership, board size, ownership concentration and debt toward ? nancial performance that measured by ROE. The population of this research is the manufacturer companies which listed at Bursa Efek Indonesia (BEI) over the ? ve years periods on 2009 until 2013. This research used purposive sampling method. The sample of this reseach consist of 90 companies that met the criteria. This study uses multiple regression analysis to see the contribution of each variable in in?uence ?nancial performance of company. The results showed that: (1) managerial ownership is not signi? cant to e? ect ? nancial performance of company, (2) board size is not signi? cant to e? ect ? nancial performance of company, (3) ownership concentration is signi? cant to e? ect ? nancial performance of company, (4) debt is signi?cant to e?ect ?nancial performance of company